Formação de educadores sexuais no curso de Ciências Biológicas da UEM : a concepção dos graduandos sobre a atuação do professor de ciências e biologia na educação sexual - Diniz, Bruna Larissa Ramalho (2015)
This thesis has its problematic organized the search design graduates of the night Degree in UEM Biological Sciences on the role of professor of science and biology in basic education and discusses family background, educational and academic graduates of this theme, in an attempt to identify possible shortcomings and obstacles to the work of these future professionals in Basic Education in the area of sexual education. The theoretical framework of this research is based mainly on studies of the formation of Sexual Educators prepared by Figueiró (1996, 2009, 2011 and 2014) in his research on the formation of science teachers in relation to Education Sexual. The research sample consisted of 12 graduates (10 females and 2 males), and 6 of the class of 3 grade and 6 class of 5 series of the course. The data collection instrument is based on semi-structured interviews, where questions are divided into four categories referring to family , school and academic education of students in issues related to sexuality and particular design they have on sexuality and Sexual education. We use as an analytical tool Discursive Textual Analysis (DTA), according to Moraes (2003) and Moraes and Galiazzi (2006). During the analysis it appears that the graduates grew up in families that almost always , they did not open to discussions about sexuality which probably accentuated the fear and shame in working the subject in the classroom. Notice also that the school received training on issues related to sexual education was based on a medical- biological approach and it happened almost always in science and biology classes, or sporadic lectures given by doctors and nurses. For them, science and biology teachers are / should be responsible for sexual education at school. It is also observed that in the course of Biological Sciences, UEM, sexuality is treated in specific subjects such as human anatomy and physiology, and sometimes in disciplines of pedagogical training area, but the approach of the theme is based solely on the aspects biological. The graduates showed up dissatisfied with training in sexual education received so far and some advocate the inclusion of a specific discipline that deals with the subject in his undergraduate course. In relation to particular conception of sexuality/sexual education, they proved to be confused about the definition of the concepts, making it clear that the medical-biological discourse, widely covered in their training, pervades the understanding that they built on the theme, which can prejudge future teaching practices. It is expected that the reflections promoted by such research is one of the ways that sex education be consolidated at school and at the University of emancipatory way.